699 Does Pre-Operative Imaging Improve Negative Appendicectomy Rate?. (12th October 2021) - Dirie, J; Merali, N; Macias, A. Maria S
Abstract: Aim: Appendicectomy is one of the most commonly performed emergency operations. There is no set guideline for an acceptable negative appendectomy rate (NAR) in the UK. Based on previous studies, a NAR of 15-30% is typically accepted. We sought to define our local practice NAR in our initial audit, introduced an appendicitis pathway based on this initial data, and then re-audited to assess whether there had been an improvement in the NAR. Method: All emergency appendicectomies carried out over a 1-year period from April 2018 – April 2019 were initially analysed. The subsequent audit analysed data from August 2020 - November 2020, after the pathway had been introduced. Histological analysis was used to determine positive or negative appendicectomy. Results: A total of 207 patients had an appendicectomy over the initial 1-year time frame. In our re-audit, 38 patients had an appendicectomy. Demographics were similar in both groups. The NAR increased from 17% to 18%. Conclusions: On first glance, the NAR does not seem to have improved. On a closer look, all patients over the age of 18 in our re-audit had a pre-operative CT, and there were no negative appendicectomies in these patients. The issue arises with younger patients, in whom justifying the radiation associated with a CT scan may be difficult. Although ultrasound does not carry the same radiation risk, previous audits at our trust have shown both its sensitivity and specificity for appendicitis is below 50%. We may have to explore alternative imaging modalities in the paediatric population or accept the higher NAR.